Análise cienciométrica em estudos genéticos com o uso da imuno-histoquímica. - Silva, Andreia Luiza Pereira (2014)
Immunohistochemistry (IHC) is a diagnostic method used to detect tissue or cellular antigens. It has been increasingly used both in research and diagnosis. The technique is used wordwide and a greater interest in the reproducibility of the method is nowadays notticed. Thus, it becomes important to address the development of applications and innovations of this technique through quantitative analysis, and also to evaluate its contribution to the Genetic field. In order to do so, there are some methodologies for assessing scientific production in a certain field, such as Scientometric Analysis. The purpose of this study was to characterize the scientific literature on the immunohistochemistry technique in the period between 1986 and 2013. We assessed trends and prospects related to the development of the method in the field of Genetics through Scientometric Analysis. A literature survey was conducted on the site Scopus, using the words immunohistochemistry*, Genetic* and molecular biology*. We used different approaches to assess the articles: publication type (experimental or review), number of articles/year, authors, field, scientific magazines, and the impact factor of journals among other factors. As a result, there was an increase in the number of publications in genetics with the use of IHC over the years followed by a stabilization, especially in developed countries like the U.S.A. There was relevant interest for the human study. Most of the research was related to study of proteins, followed by ribonucleic acid (RNA). The main pathology associated with immunohistochemical studies was cancer, supporting its use as an important tool in the pathology laboratory.